Convergent evolution of two mammalian neuronal enhancers by sequential exaptation of unrelated retroposons - Franchini, L.F. (2011)
The proopiomelanocortin gene (POMC) is expressed in a group of neurons present in the arcuate nucleus of the hypothalamus. Neuron-specific POMC expression in mammals is conveyed by two distal enhancers, named nPE1 and nPE2. Previous transgenic mouse studies showed that nPE1 and nPE2 independently drive reporter gene expression to POMC neurons. Here, we investigated the evolutionary mechanisms that shaped not one but two neuron- specific POMC enhancers and tested whether nPE1 and nPE2 drive identical or complementary spatiotemporal expression patterns. Sequence comparison among representative genomes of most vertebrate classes and mammalian orders showed that nPE1 is a placental novelty. Using in silico paleogenomics we found that nPE1 originated from the exaptation of a mammalian- apparent LTR retrotransposon sometime between the metatherian/ eutherian split (147 Mya) and the placental mammal radiation (≈90 Mya). Thus, the evolutionary origin of nPE1 differs, in kind and time, from that previously demonstrated for nPE2, which was exapted from a CORE-short interspersed nucleotide element (SINE) retroposon before the origin of prototherians, 166 Mya. Transgenic mice expressing the fluorescent markers tomato and EGFP driven by nPE1 or nPE2, respectively, demonstrated coexpression of both reporter genes along the entire arcuate nucleus. The onset of reporter gene expression guided by nPE1 and nPE2 was also identical and coincidental with the onset of Pomc expression in the presumptive mouse diencephalon. Thus, the independent exaptation of two unrelated retroposons into functional analogs regulating neuronal POMC expression constitutes an authentic example of convergent molecular evolution of cell-specific enhancers.